Countering illegibility: Religion, ethnicity and sexuality in public debates and lived experience in Belgium - Brandt, Nella van den (Culture and religion, 2018)
In this article, I set out to explore various intersectional social constructions of ethnicity, religion and sexuality. First, I conduct an analysis of recent public controversies in Flanders (Belgium) about women's and (homo)sexual equality as set against religious authorities and religious-ethnic minorities. It reveals how dominant understandings of ethnicity, sexuality and religion are constructed, reinforced and, if needed, defended. Second, I foreground a critical counter-voice negotiating these what I call ethno-sexular' boundary constructions. I analyse the lived experiences of Hajar, a volunteer of an antiracist LGBTQI organisation located in Brussels, and argue that because of a dominant ethno-sexular discourse, Hajar's hybrid identifications and critical voice is made illegible in much of her social environment.